Minimally Invasive Treatment of Recurrent Varicose Veins with Thrombotic Complications - Serhii P. Shchukin (Ukrainian Journal of Cardiovascular Surgery, 2025)
Background. Recurrent varicose vein disease (RVVD) remains a frequent problem after surgery or endovenous ablation (≈13-65 %). Mechanisms include residual reflux, de novo varicosities, and neovascularization. When RVVD is complicated by superficial vein thrombosis (SVT), treatment becomes challenging because current guidelines focus mainly on anticoagulation and rarely address reflux correction.Aim. To evaluate the feasibility, safety, and effectiveness of combined minimally invasive therapy for RVVD complicated by SVT.Materials and Methods. This single-center cohort included 31 patients (24 women, 7 men; mean age 55±13 years) with duplex-verified SVT and RVVD (CEAP C2r–C6r) treated between 2013 and 2025. Interventions comprised endovenous laser or radiofrequency ablation (EVLA/RFA), ultrasound-guided foam sclerotherapy (UGFS), and miniphlebectomy (MF), individually or in combination. Short-term rivaroxaban (15-20 mg/day for 20-45 days) was prescribed for SVT. Primary endpoints: segment occlusion, reflux elimination, thrombus regression, recurrence, and complications (EHIT/DVT/PE). Secondary endpoints: changes in VCSS, CIVIQ-14, VDS, and VDSS.Results. Great saphenous vein (GSV) reflux occurred in 20 (65 %) patients, small saphenous vein (SSV) reflux in 15 (48 %) patients, and perforator incompetence in 23 (74 %). Neovascularization at the SFJ/SPJ was detected in 10 (32 %), confirming true recurrence. EVLA was performed in 29/31 patients, usually with UGFS ± MF. Clinical improvement was significant: mean VCSS decreased from 5.5 to 2.1, and CIVIQ-14 from 35.2 to 22.2 (p<0.001). No EHIT ≥ II, DVT, or PE occurred. Duplex confirmed thrombus regression in 94 % of cases.Conclusions. Combined minimally invasive treatment (EVLA/RFA + UGF±MF) is a feasible, safe, and effective option for RVVD complicated by SVT. This reflux-directed, office-based approach ensures durable anatomic success, rapid recovery, and meaningful quality-of-life improvement.